Enhancing predictive accuracy of the cardiac risk score in open abdominal aortic surgery: the role of left ventricular wall motion abnormalities - Djokic, Ivana; Milicic, Biljana; Matic, Predrag; Ilijevski, Nenad; Milojevic, Milan; Jovic, Miomir (Frontiers in Cardiovascular Medicine, 2023)
Background Open abdominal aortic surgery carries many potential complications, with cardiac adverse events being the most significant concern. The Vascular Study Group Cardiac Risk Index (VSG-CRI) is a commonly used tool for predicting severe cardiac complications and guiding clinical decision-making. However, despite the potential prognostic significance of left ventricular wall motion abnormalities (LVWMAs) and reduced LV ejection fraction (LVEF) for adverse outcomes, the VSG-CRI model has not accounted for them. Hence, the main objective of this study was to analyze the added value of LV wall motion on the discriminatory power of the modified VSG-CRI in predicting major postoperative cardiac complications. Methods A prospective study was conducted involving 271 patients who underwent elective abdominal aortic surgery between 2019 and 2021. VSG-CRI scores were calculated, and preoperative transthoracic echocardiography was conducted for all patients. Subsequently, a modified version of the VSG-CRI, accounting for reduced LVEF and LVWMAs, was developed and incorporated into the dataset. The postoperative incidence of the composite endpoint of major adverse cardiac events (MACEs), including myocardial infarction, clinically relevant arrhythmias treated with medicaments or by cardioversion, or congestive heart failure, was assessed at discharge from the index hospitalization, with adjudicators blinded to events. The predictive accuracy of both the original and modified VSG-CRI was assessed using C-Statistics. Results In total, 61 patients (22.5%) experienced MACEs. Among these patients, a significantly higher proportion had preoperative LVWMAs compared to those without (62.3% vs. 32.9%, p < 0.001). Multivariable regression analysis revealed the VSG-CRI [odds ratio (OR) 1.46, 95% confidence interval (CI) 1.21–1.77; p < 0.001] and LVWMA (OR 2.76; 95% CI 1.46–5.23; p = 0.002) as independent predictors of MACEs. Additionally, the modified VSG-CRI model demonstrated superior predictability compared to the baseline VSG-CRI model, suggesting an improved predictive performance for anticipating MACEs following abdominal aortic surgery [area under the curve (AUC) 0.74; 95% CI 0.68–0.81 vs. AUC 0.70; 95% CI 0.63–0.77; respectively]. Conclusion The findings of this study suggest that incorporating preoperative echocardiography can enhance the predictive accuracy of the VSG-CRI for predicting MACEs after open abdominal aortic surgery. Before its implementation in clinical settings, external validation is necessary to confirm the generalizability of this newly developed predictive model across different populations.